SOSIALISASI PEMULIHAN LEARNING LOSS PASCA BENCANA GEMPA BUMI PADA SISWA SMA PRIMA TELADAN MELALUI PENDEKATAN ABCD METHOD DI DESA MANGUNKERTA KECAMATAN CUGENANG KABUPATEN CIANJUR - Mulyati, Yuyun; Prabowo, Danu Aji (Universitas Al Ghifari, 2024)
The impact of the earthquake that hit Cianjur resulted in significant disruption to the learning process. This incident gave rise to a phenomenon called learning loss among students which has the potential to affect long-term academic achievement. Through KKN activities, MBKM raised the issue of learning loss and discussed post-disaster recovery efforts using the Asset-Based Community Development (ABCD Method) approach. The ABCD Method is implemented with four activity stages, namely: discovery, dream, design, define. This asset-based development is one way to improve the quality of society in supporting prosperity. The essence of the ABCD concept is to carry out community empowerment by utilizing the potential of the community. Moving from potential, ways will be developed to realize people's own dreams, namely prosperity. The ABCD method emphasizes the utilization of local resources and potential which is used to identify and optimize existing assets, including the involvement of teachers, parents and local communities in supporting the learning process. The results of research through the MBKM KKN program show that the ABCD approach is effective in facilitating educational recovery through adaptive and community-based learning programs, significantly reducing the impact of learning loss on students. This article also provides recommendations for wider implementation of the ABCD approach in the context of post-disaster education recovery in other earthquake-prone areas